Achieving higher performing primary care through patient registration: A review of twelve high-income countries. Issue 12 (December 2021) - Marchildon, Gregory P.; Brammli-Greenberg, Shuli; Dayan, Mark; De Belvis, Antonio Giulio; Gandré, Coralie; Isaksson, David; Kroneman, Madelon; Neuner-Jehle, Stefan; Saunes, Ingrid Sperre; Thomas, Steven; Vrangbæk, Karsten; Quentin, Wilm
Highlights: Patient registration initially emerged as part of the introduction of universal health coverage systems. Subsequent patient registration reforms aimed at improving integration, coordination and efficiency of health services. Considerable potential for greater use of patient registration in future reforms. Abstract: Background: Patient registration with a primary care providers supports continuity in the patient-provider relationship. This paper develops a framework for analysing the characteristics of patient registration across countries; applies this framework to a selection of countries; and identifies challenges and ongoing reform efforts. Methods: 12 jurisdictions (Denmark, France, Germany, Ireland, Israel, Italy, Netherlands, Norway, Ontario [Canada], Sweden, Switzerland, United Kingdom) were selected for analysis. Information was collected by national researchers who reviewed relevant literature and policy documents to report on the establishment and evolution of patient registration, the requirements and benefits for patients, providers and payers, and its connection to primary care reforms. Results: Patient registration emerged as part of major macro-level health reforms linked to the introduction of universal health coverage. Recent reforms introduced registration with the aim of improving quality through better coordination and efficiency through reductions in unnecessary referrals. Patient registration is mandatory only in three countries. Several countries achieve high levels of registration by using strong incentives for patients and physicians (capitation payments). Conclusion: Patient registration means different things in different countries and policy-makers and researchers need to take into consideration: the history and characteristics of the registration system; the use of incentives for patients and providers; and the potential for more explicit use of patient-provider agreements as a policy to achieve more timely, appropriate, continuous and integrated care.